2013
DOI: 10.1097/acm.0b013e3182a36cab
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Electronic Health Records as an Enabler of Hospital Quality and Patient Satisfaction

Abstract: This study evaluated the effectiveness of the U.S. federal government's investment in hospital information technology infrastructure. Results suggest that the most advanced EHRs have the greatest payoff in improving clinical process of care scores, without detrimentally impacting the patient experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 8 publications
0
39
0
Order By: Relevance
“…While our surgeons were satisfi ed with the choice of EHR and did not feel that it negatively impacted them personally, they indicated concern regarding the effect on patient satisfaction. In a cross-sectional retrospective analysis of hospitals under the Medicare Hospital Value-Based Purchasing Program, use of "advanced" EHRs did not detrimentally impact the patient experience (12). A separate multistudy review showed a positive or neutral assessment of patient experience with EHR use (13).…”
Section: Discussionmentioning
confidence: 99%
“…While our surgeons were satisfi ed with the choice of EHR and did not feel that it negatively impacted them personally, they indicated concern regarding the effect on patient satisfaction. In a cross-sectional retrospective analysis of hospitals under the Medicare Hospital Value-Based Purchasing Program, use of "advanced" EHRs did not detrimentally impact the patient experience (12). A separate multistudy review showed a positive or neutral assessment of patient experience with EHR use (13).…”
Section: Discussionmentioning
confidence: 99%
“…Explain what they are doing on computer (22) BHe puts something in the computer and then he'll explain to me what he's putting in.^118 (n = 15)…”
Section: Discussionmentioning
confidence: 99%
“…7 While most demonstrated a lack of change in the patient-provider relationship and high satisfaction with EMR use, concerns such as provider distraction by the computer and changes in non-verbal aspects of communication such as eye contact and long periods of silence were raised. [17][18][19][20][21][22][23] In addition, most studies were conducted prior to the 2013 Meaningful Use ACA mandates and rapid EMR adoption. 7 As more patients encounter their physicians using EMRs in the exam room after ACA implementation, they may be better primed to share their experiences on this timely issue.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial strides have been made to study the success of HITs and their impact on patient care outcomes like care quality, patient satisfaction, and increased likelihood of adherence to medications [2][3][4][5] . But with the increase in data breaches and privacy concerns 6 , success of HITs is now also contingent on how well the privacy of patient medical data is secured.…”
Section: Introduction Backgroundmentioning
confidence: 99%